PENGARUH EMPLOYEE ENGAGEMENT, KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN RUMAH SAKIT ROYAL PROGRESS JAKARTA - Fariz Wekatama Heriansyah (2022)
This study aims to prove and determine the effect of employee engagement, competence, and job satisfaction on employee performance partially and simultaneously. This research is a quantitative research using primary data sources. In this study, a sample of 50 employees of the customer service divison unit Royal Progress Hospital Jakarta used the saturated sample method. The data of this study were obtained using a questionnaire which was measured using a Likert scale. The data analysis technique used is descriptive and inferential analysis using SmartPLS 3.0 software. The results of this study indicate that employee engagement has a positive and significant effect on employee performance of 2,361, competence has a positive and significant effect on employee performance of 2,171, and job satisfaction has a positive and significant effect on employee performance of 2,693, as well as employee involvement, competence, and satisfaction. work. simultaneous influence on employee performance of 25,875.Keywords: employee engagement, competence, job satisfaction, and employee performance.